Laser surface modification of porous yttria stabilized zirconia against CMAS degradation. Issue 5 (1st April 2020) - Bakkar, S.; Pantawane, M.V.; Gu, J.J.; Ghoshal, A.; Walock, M.; Murugan, M.; Young, M.L.; Dahotre, N.; Berman, D.; Aouadi, S.M.
Abstract: Here, we present a new combined freeze-casting and laser processing method for the design of yttria-stabilized zirconia (YSZ) based thermal-barrier coatings. YSZ ceramics with unidirectionally-aligned pore channels were created using the freeze-casting method. After sintering, top view and cross-sectional scanning electron microscopy (SEM) revealed the structural features of the preform, which exhibits a 74 ± 2% volume fraction of porosity and an average pore channel size of 30 ± 3 μm. The measured thermal conductivity of this porous structure was 0.27 ± 0.02 W/(m K), which is eight times lower than that of reported values for dense YSZ. Though high porosity is beneficial both from a structural and thermal response perspective, the open porosity could potentially be an issue from an application stand-point when evaluating the resistance of materials to calcium–magnesium–aluminum–silicon oxide (CMAS) attack. CMAS attack, which can originate from deposits of molten sand, ash, and dust, is one of the major causes of thermal barrier coating failure. Therefore, the surface of the porous samples was modified using a laser process to create a barrier to CMAS infiltration. SEM micrographs aided in determining the optimum laser parameters required to fully seal the surface using a laser treatment. The performance of the original porous and surface-modified YSZ was compared by conducting CMAS infiltration studies. Laser modification was shown to be a viable technique to significantly reduce CMAS infiltration in porous thermal barrier coatings.